2002
DOI: 10.1676/0043-5643(2002)114[0324:acrtsp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Avian Community Response to Southern Pine Ecosystem Restoration for Red-Cockaded Woodpeckers

Abstract: The effects of Red-cockaded Woodpecker (Picoides borealis) management on nontarget birds is not widely known. Intensive management for pine specialists such as the Red-cockaded Woodpecker may negatively impact both Nearctic-Neotropical and Temperate Zone migrants associated with hardwood vegetation. To evaluate possible positive and negative associations, we surveyed avian communities from 1995-1997 using point counts within managed Red-cockaded Woodpecker cavity tree clusters and mature forest control sites i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 18 publications
(19 reference statements)
0
13
0
Order By: Relevance
“…Shortleaf pine restoration leads to increased levels of plant available nutrients over time [22], in spite of initial loss of nitrogen [23]. Shortleaf pine restoration also provides important habitat for the federally endangered red-cockaded woodpecker (Picoides borealis), and also positively impacts diversity and/or abundance of populations of taxa including butterflies, reptiles, amphibians [24], other birds [25,26] and small mammals [27]. Shortleaf pine stands, characterized by relatively frequent fire maintaining low basal area, also provide important habitat for endangered Indiana bats (Myotis sodalis) [28], as well as a number of other bat species [29].…”
Section: Shortleaf Pine Restorationmentioning
confidence: 99%
“…Shortleaf pine restoration leads to increased levels of plant available nutrients over time [22], in spite of initial loss of nitrogen [23]. Shortleaf pine restoration also provides important habitat for the federally endangered red-cockaded woodpecker (Picoides borealis), and also positively impacts diversity and/or abundance of populations of taxa including butterflies, reptiles, amphibians [24], other birds [25,26] and small mammals [27]. Shortleaf pine stands, characterized by relatively frequent fire maintaining low basal area, also provide important habitat for endangered Indiana bats (Myotis sodalis) [28], as well as a number of other bat species [29].…”
Section: Shortleaf Pine Restorationmentioning
confidence: 99%
“…Although bird richness can be high in pine-hardwood forests, several authors (Wilson et al, 1995;Gordon et al, 2001;Conner et al, 2002;Provencher et al, 2002) have reported benefits to bird communities from restoring these sites to pine-grassland systems. In plantations, fire applied alone or following herbicide or mechanical treatments can promote more diverse and abundant bird populations (Conner et al, 2002), including breeding birds of high conservation priority (Gordon et al, 2001).…”
Section: Stand Scalementioning
confidence: 99%
“…The red‐cockaded woodpecker requires large tracts of mature pine stands, and it is also a keystone species because it excavates nesting cavities that are often used subsequently by other species (Blanc & Walters, ). Thus, the bird serves as an umbrella species because restoration activities focusing on the red‐cockaded woodpecker have been shown to provide benefits to whole communities (Conner et al ., ).…”
Section: Introductionmentioning
confidence: 97%